Mapping the Cultural Tourism Complex of Nagari Pariangan Using UAV and Geographic Information Systems - Arif Rizky Pradana; Fajrin Fajrin; Ilham Armi (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
The development of spatial data utilization has increased dramatically in the past decade. This is related to the widespread use of Geographic Information Systems (GIS) and the advancement of technology in acquiring spatial data. High-tech tools like UAVs (Unmanned Aerial Vehicles) are increasingly integrated with Geographic Information Systems (GIS) and other surveying and mapping technologies, and are therefore used in various surveying, mapping, and spatial analysis projects. One of the advantages of UAVs is that the captured data can be processed through software, producing images with high spatial and temporal resolution. The use of this technology demonstrates that mapping can be performed using photographic data. The purpose of this research is to analyze and map the distribution of cultural tourism sites in detail using UAV and GIS in Nagari Tuo Pariangan, Tanah Datar Regency. Based on the results of the research, it can be concluded that data collection was carried out using a DJI Mavic Pro drone, capturing 228 aerial photos which were then exported into orthophotos. Orthophotos function as a reference for the distribution map of cultural tourism sites. In addition, a database was created, integrating spatial (geographic) and non-spatial (attribute) data, containing the necessary information for tourism objects, such as the owner's name, year of construction, function, and history of the object. There are 31 cultural tourism objects in Nagari Pariangan, Tanah Datar Regency, consisting of 8 Rumah Gadang (traditional houses), 11 Surau (small mosques), 3 hot spring pools, 3 stone inscriptions, 1 hot spring pool, 1 Tuo Pariangan Mosque, 1 river, 1 Tabuik Mosque, and 1 Saruang Hall. Most of these cultural tourism objects are well-maintained by their owners, while a small number are neglected due to a lack of adequate human resources.